Concussion Education in the School Setting: A Scoping Review. (8th March 2022) - Mallory, Kylie D.; Saly, Lauren; Hickling, Andrea; Colquhoun, Heather; Kroshus, Emily; Reed, Nick
ABSTRACT: BACKGROUND: Concussions are a prevalent injury among youth, and concussion education has the potential to promote positive concussion‐related behaviors. Recent recommendations and legislation have increased concussion education provided in schools; however, little is known about the education context, delivery method, development, and evaluation. A scoping review was conducted to identify peer‐reviewed literature on concussion education delivered in the school setting. METHODS: Six databases were searched (MEDLINE, CINAHL, EMBASE, PsycINFO, SPORTDiscus, and ERIC) to identify published articles from 2002 to July 16, 2020 that delivered concussion education in the school setting. Included studies described the concussion education and were written in English. RESULTS: A total of 11, 373 articles were identified and screened, with 27 studies meeting eligibility criteria and therefore, included. The studies delivered education to various stakeholders including students (n = 12; 44.4%), coaches (n = 5; 18.5%), educators (n = 3; 11.1%), parents (n = 1; 3.7%), and a mixed audience (n = 6; 22.2%). The education format varied and six studies (22.2%) developed the education based on a theory, model, or framework. CONCLUSIONS: This study found substantial variability in the context, delivery method, development, and evaluation of education delivered in schools and further evaluation of this education is needed to ensure it is best‐suited for school‐based stakeholders.